2002
DOI: 10.1002/jmor.10030
|View full text |Cite
|
Sign up to set email alerts
|

Comparative observations on corneas, with special reference to bowman's layer and descemet's membrane in mammals and amphibians

Abstract: Corneas of tadpole, mouse, rat, guinea pig, rabbit, cat, cattle, and human were examined by TEM and SEM in a comparative study. The differences between species were noted mainly by using TEM. Bowman's layer showed a tendency to be well developed in higher mammals. Tadpoles lack a Bowman's layer, lower mammals have a thin Bowman's layer, and higher mammals have a thick Bowman's layer. The boundary between the substantia propria and Descemet's membrane was distinct in higher mammals. On the other hand, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 7 publications
6
97
0
7
Order By: Relevance
“…Examples include the fact that the blink rate in both mice and rabbits is lower than that in humans; 182,183 humans also have a much higher concentration of lysozyme in their tears. 184 Rabbits possess a nictitating membrane, and the structure of a human cornea is different in several ways to that of mice and rabbits: Bowman's layer and Descemet's membrane are thicker, 185 the orientation of the collagen is different 186 and the depth of each of the layers varies depending on species. 187 On a molecular level, examples of species differences include the fact that mice are known to use several NAIP accessory proteins to activate the NLRP4 inflammasome, whereas in humans only one type of NAIP has been found.…”
Section: The Relevance Of Animal Models Of Keratitismentioning
confidence: 99%
“…Examples include the fact that the blink rate in both mice and rabbits is lower than that in humans; 182,183 humans also have a much higher concentration of lysozyme in their tears. 184 Rabbits possess a nictitating membrane, and the structure of a human cornea is different in several ways to that of mice and rabbits: Bowman's layer and Descemet's membrane are thicker, 185 the orientation of the collagen is different 186 and the depth of each of the layers varies depending on species. 187 On a molecular level, examples of species differences include the fact that mice are known to use several NAIP accessory proteins to activate the NLRP4 inflammasome, whereas in humans only one type of NAIP has been found.…”
Section: The Relevance Of Animal Models Of Keratitismentioning
confidence: 99%
“…Early work on the cornea showed that, unlike humans, the rat has no Bowman's layer (Jakus 1954). Recently, however, the somewhat disorganized anteriormost stroma extending a few fibrils beneath the lamina densa in the rat has been referred to as a very thin and indistinct Bowman's layer (Hayashi et al 2002). However, there are significant differences between the dense fibrillar meshwork that constitutes Bowman's layer in humans, which is up to 12 mm thick (Komai & Ushiki 1991), and the slightly disorganized stroma immediately beneath the epithelial basement membrane in the rat cornea (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Non-myelinated nerve axons penetrate BL irregularly across the cornea to ultimately provide epithelial innervation. Bowman's layer is well developed in higher mammals (cattle), lower mammals (rodents) have a thin BL and tadpoles completely lack BL [37]. BL does not regenerate after injury, but injuries to this layer are often replaced by disordered, collagenous scar tissue [38].…”
Section: Bowman's Layermentioning
confidence: 99%
“…Previous measurements of human BL thickness have had widely varying results, ranging from 8 to 17.7µm, depending on the type of measurement (in vivo or ex vivo), tissue preparation method, and the measurement technique used. The techniques used to date include light microscopy (LM) [4], transmission electron microscopy (TEM) [37,40], tandem scanning confocal microscopy (TSCM) [41], and spectral domain optical coherence tomography (SD-OCT) [42] (Table 1). …”
Section: Bowman's Layermentioning
confidence: 99%